The effects of L-Citrulline and Glutathione on Endurance performance in young adult trained males - Hannah E. Cabre; Casey E. Greenwalt; Lacey M. Gould; Abbie E. Smith-Ryan (Taylor & Francis Group, 2023)
Background Citrulline may amplify the effects of L-arginine and nitric oxide concentration, which may augment vasodilation and blood flow, thereby enhancing aerobic exercise performance. The purpose of this randomized, double-blind, placebo-controlled crossover study was to investigate effects of L-citrulline + Glutathione on aerobic exercise performance and blood flow in well-trained men. Methods Twenty-five males (Mean ± SD; Age: 22.2 ± 2.4 yrs; Height: 177.0 ± 4.8 cm; Weight: 75.3 ± 6.9 kg) were randomly assigned to the L-citrulline + Glutathione (Setria Performance Blend: SPB; L-citrulline [2 g] + glutathione [200 mg], 6 capsules) or placebo (PL; 3.1 g cellulose, 6 capsules) group. Participants performed a maximal oxygen consumption treadmill test to determine peak velocity (PV) and returned after eight days of ingesting either PL or SPB. Three timed treadmill runs to exhaustion (TTE) were performed at 90%, 100%, and 110% PV. Brachial artery blood flow and vessel diameter were assessed using ultrasound at 1-hr prior to exercise (1hrPrEX), after each exercise bout, immediately post-exercise (immediate PEX), and 30 minutes post exercise (30minPEX) at visits 2 and 4. Blood analytes were assessed via venous blood draws at visit 1, visit 3, and 1hrPEX, immediate PEX, and 30minPEX at visits 2 and 4. After a 14-day washout, participants repeated the same procedures, ingesting the opposite treatment. Separate repeated measures ANOVAs were performed for TTE, vessel diameter, blood flow, and blood analytes. Results Blood flow was significantly augmented 30minPEX (p = 0.04) with SPB in comparison with PL. L-citrulline and L-arginine plasma concentrations were significantly elevated immediately PEX (p = 0.001) and 30-minPEX (p = 0.001) following SPB in comparison to PL. Conclusion Acute ingestion of SPB after eight days may enhance blood flow, L-citrulline, and L-arginine plasma concentrations after high-intensity exercise, which may enhance performance. Clinical Trial Registration [https://clinicaltrials.gov/ct2/show/nct04090138], identifier [NCT04090138].